Micropulse diode laser trabeculoplasty in Nigerian patients - Babalola OE (Dove Medical Press, 2015)
Olufemi Emmanuel Babalola1,2 1Rachel Eye Center, Abuja, Nigeria; 2Department of Ophthalmology, College of Health Sciences, Bingham University, New Karu, Nigeria Introduction: The term micropulse laser trabeculoplasty suggests that only a fraction of the laser power is applied to the trabeculum to effect pressure lowering. It has not yet been exclusively used in Negroes, and we wish to report on our experience in Nigerian patients.Methods: The study design is a retrospective chart review of our patients at the Rachel Eye Center in Abuja. The 810 diode Optos FastPulse laser was used to apply 34 cycles of treatment to 30 eyes of 16 individuals. Patients were selected based on the failure of maximal medical therapy. One patient had two extra rounds of treatment, while two patients were treated in only one eye. The pressure change at 1 hour after the treatment was analyzed. Patients were followed up for a mean period of 160 days with continuous monitoring of pressure changes. Patients’ original therapy was not disturbed.Results: Postlaser immediate drop in intraocular pressure (IOP) averaged 3.2 mmHg (CI 1.6–4.7, P<0.0001) representing 17.2% drop from baseline prelaser IOP. The drop in IOP was sustained over varying periods, from a few weeks to several months. There was a temporary spike in three instances. No serious side effects were noted.Conclusion: Micropulse diode laser trabeculoplasty is a useful adjunct in the management of open-angle glaucoma in Nigerians. This corroborates the findings of other researchers in western populations. Keywords: micropulse, diode laser, Nigeria, glaucoma